Five-minute heart rate variability can predict obstructive angiographic coronary disease. Issue 5 (25th November 2011) - Kotecha, D; New, G; Flather, M D; Eccleston, D; Pepper, J; Krum, H
Abstract : Objective: Obstructive coronary artery disease (CAD) is evident in only half of patients referred for diagnostic angiography. Five-minute heart rate variability (HRV) is a non-invasive marker for autonomic control of the vasculature, which this study hypothesised could risk-stratify cardiac patients and reduce unnecessary angiograms. Design: A prospective observational study (the Alternative Risk Markers in Coronary Artery Disease (ARM–CAD) study). Setting: Three cardiac centres in Melbourne, Australia. Patients: 470 consecutive patients undergoing elective angiography (with predominantly normal cardiac rhythm), regardless of co-morbidity. Main outcome measures: The presence of obstructive CAD (≥50% stenosis) on angiography. Results: Patients with obstructive CAD had significantly reduced HRV, particularly in the low frequency (LF) range (median 180 vs 267 ms 2 without CAD; p<0.001). There was a linear trend with the severity of CAD; median LF power (IQR) in patients with normal coronaries was 275 (612), with minor coronary irregularities 255 (400), single-vessel CAD 212 (396) and more severe disease 170 (327) ms 2 ; p value for trend 0.003. There was a similar reduction in LF power regardless of the anatomical location of coronary stenoses. Comparing patients with LF less than 250 and 250 ms 2 or greater, the adjusted OR for obstructive CAD using multivariate regression was 2.42, 95% CI 1.33 to 4.38 (p=0.004). No interactions were noted in subgroup analysis and HRV added to risk prediction irrespective of the baseline Framingham risk (p<0.0001). Conclusion: Low HRV is strongly predictive of angiographic coronary disease regardless of other co-morbidities and is clinically useful as a risk predictor in patients with sinus rhythm. Clinical trial registration information: http://clinicaltrials.gov/ct2/show/NCT00403351 www.armcad.com